CHARACTERIZATION OF VirB4 PROTEIN OF LOCAL ISOLATE Brucella abortus WITH WESTERN BLOTTING TECHNIQUE - Praja, Ratih Novita; Handijatno, Didik; Koesdarto, Setiawan; Yudhana, Aditya (Universitas Syiah Kuala, 2018)
This research aimed to characterize VirB4 protein of local isolate Brucella abortus with Western blotting method. The result showed that there were four protein bands with molecular weights of 64.61, 59.25, 21.63, and 16.70 kDa by triggering a reaction between the whole Brucella abortus and anti-Brucella abortus serum. The results also revealed that there was only one protein band with a molecular weight of 59.25 kDa triggering a reaction between the whole Brucella abortus and anti-VirB Brucella abortus serum. Finally, it can be concluded that VirB4 protein can affect the virulence factor of Brucella abortus, successfully characterized with the appearance of one band with a molecular weight of 59.25 kDa by using Western blotting method.